PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA RODA PUTAR TERHADAP HASIL BELAJAR MATEMATIKA KELAS IV SD - Novita Sari; Jayanti Jayanti; Ida Suryani (Universitas Negeri Medan, 2023)
Abstract: The purpose of this research is to ascertain how rotary wheel media and the stad cooperative learning model affect the mathematics learning outcomes of fourth grade elementary school students. This exploration is a trial investigation of the Genuine Exploratory Plan structure with the plan utilized is Presest-Posttest Control Gathering Plan. There are ten multiple-choice questions on the test. The participants in this study were all SD Negeri 1 Babat grade IV students. The examples in this review were class IV.1 (Control) and Class IV.3 (Examination) with a sum of 48 understudies, class IV.1 upwards of 23 understudies and class IV.3 25 understudies. Information assortment is done involving tests as pretest and posttest. In light of the speculation test esteem and posttest consequences of exploratory and control class understudies, a determined cost = 3.438 and a table worth of 1.679 with α = 0.05 and df = 46, then 3.438 ≥ 1.679 then H0 is dismissed and Ha is acknowledged. Therefore, it can be concluded that rotary wheel media and the STAD cooperative learning model have an effect on the mathematics learning outcomes of fourth-grade elementary school students.Keyword: STAD Type Cooperative Model, Swivel Wheel, mathAbstrak: Kajian ini diharapkan dapat menentukan dampak Hasil belajar IPA siswa kelas IV SD dibantu dengan model pembelajaran helpfull tipe stad dan media roda putar. Desain yang digunakan dalam penelitian ini adalah Presest-Posttest Control Group Design yang merupakan desain true eksperimental. Tes terdiri dari 10 pertanyaan sebagai banyak keputusan. Peserta penelitian ini adalah seluruh siswa kelas IV SD Negeri 1 Babat. Kelas IV.1 (Kontrol) dan Kelas IV.3 (Eksperimen) menjadi sampel penelitian. Jumlah siswa di kelas IV.3 sebanyak 24 siswa, dan di kelas IV.1 sebanyak 48 siswa. Pemilahan informasi dilakukan dengan melibatkan tes sebagai pretest dan posttest. Harga thitung adalah 3,438, dan nilai ttabel adalah 1,679, dengan = 0,05 dan df = 46. Jika 3,438 1,679, maka H0 ditolak dan Ha diterima berdasarkan hasil posttest yang dilakukan siswa pada eksperimen dan kontrol kelas. Sehingga cenderung Dapat disimpulkan bahwa model pembelajaran menyenangkan tipe STAD berbantuan media roda putar berpengaruh terhadap hasil belajar siswa kelas IV SD.Kata Kunci: Model Kooperatif Tipe STAD, Roda Putar, matematika